The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/5936171
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Profiling and Bioinformatic Modeling Identify Its Regulatory Role in Hepatic Steatosis

Abstract: Circular RNAs (circRNAs) exhibit a wide range of physiological and pathological activities. To uncover their role in hepatic steatosis, we investigated the expression profile of circRNAs in HepG2-based hepatic steatosis induced by high-fat stimulation. Differentially expressed circRNAs were subjected to validation using QPCR and functional analyses using principal component analysis, hierarchical clustering, target prediction, gene ontology (GO), and pathway annotation, respectively. Bioinformatic integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 47 publications
1
58
0
Order By: Relevance
“…CircRNAs are an evolutionarily conserved class of non-coding RNAs [29] which were reported to be remarkably enriched in the nervous system [30] and play roles in brain function [21,31,32]. To identify key circRNAs that correlated with Nrf2-mediated neuroprotection in the brain, DEcircRNAs in the substantia nigra and corpus striatum tissues between Nrf2 (-/-) and Nrf2 (+/+) mice were identified by microarray and bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are an evolutionarily conserved class of non-coding RNAs [29] which were reported to be remarkably enriched in the nervous system [30] and play roles in brain function [21,31,32]. To identify key circRNAs that correlated with Nrf2-mediated neuroprotection in the brain, DEcircRNAs in the substantia nigra and corpus striatum tissues between Nrf2 (-/-) and Nrf2 (+/+) mice were identified by microarray and bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated the close relationship between circRNAs with hepatic steatosis and NASH, and circRNAs can regulate the cancer cell growth, proliferation, migration and invasion. Guo et al [3] have reported the dysregulation of circRNAs is related to the hepatic steatosis. To date, not many researchers have paid su cient attention to the important role of circRNAs in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the occurrence of NAFLD has increased at an alarming rate with the rapid growth of obesity in the population. There is growing evidence that NAFLD can be caused by multiple factors, including lipid accumulation in liver, mitochondrial dysfunction, a high fat diet, insulin resistance and genetic factors [3]. Although the underlying mechanism of NAFLD has not been completely explained, recent researches have suggested to nd out potential biomarkers that might be able to do early prediction and diagnosis for patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these differential circRNAs (hsa_circRNA_070616, hsa_circRNA_103716, hsa_circRNA_104854, hsa_circRNA_004183, hsa_circRNA_044353) are reported expressed in the mammalian brain [24]. Li et al [25] have reported that hsa_circRNA_004183 play an important regulatory role in hepatic steatosis, but there is no report about the detailed mechanism. Hsa_circRNA_070616 and hsa_circRNA_103716 are selected for further analysis because they are both predicted as sponge of hsa-miR-574-5p.…”
Section: Discussionmentioning
confidence: 99%